SMS Translator Bahasa Indonesia - Bahasa Jawa Menggunakan Teknologi J2ME - Nur Alfi Ekowati; Yusmedi Nurfaizal; Nandang Hermanto (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
SIL (Summer Institute of Linguistics) data showthat among 735 local languages in Indonesia, there are 652languages in an alarming condition, not known, even 2languages of them are extinct. Particularly, Bahasa Jawa asan original language spoken by the people from Central Javaprovince is less desirable as the daily communicationlanguage of its younger generation. This is conformable bythe results of a survey to a number of representative studentsfrom all of the state senior high schools (SMA negeri) in aregion in the Central Java, namely Purwokerto. It proves thatthe students who represent the young people in the areacannot master the well-usage of Bahasa Jawa correctly.Whereas, the language is very important to havecommunication with the elder people. The application of SMStranslator from Bahasa Indonesia to Bahasa Jawa isdeveloped to help solving the problem.